Pengaruh Kepemimpinan Kepala Sekolah, Sarana Prasarana dan Komunikasi antar Personal terhadap Kinerja Guru SMP Negeri di Kecamatan Ulim Kabupaten Pidie Jaya - Salisah, Salisah; Luthfi, Luthfi (peusangan, 2023)
This study aims to analyze and obtain empirical answers about the influence of the principal's leadership, aspects of school infrastructure and interpersonal communication in the school environment on efforts to improve teacher performance. This research was in the form of a survey using a questionnaire to 75 state junior high school teachers in Ulim District, Pidie Jaya Regency. The research method is an associative description with analysis and hypothesis testing with a path analysis approach. The results of the study found that (a) there was an influence of the Principal's Leadership on teacher performance of 11.40%. (b) It is proven that there is an influence of school infrastructure in completing work and teaching problems on teacher performance of 13.77%. (c) there is an influence of communication that exists between teachers and also with leaders in schools on teacher performance by 17.85 percent. (d) Simultaneously there is an influence of the Principal's Leadership, Infrastructure and Interpersonal Communication on Teacher Performance by 43%.